2012
DOI: 10.1038/oncsis.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the AKT/cyclin D1/Cdk4 survival signaling pathway in radioresistant cancer stem cells

Abstract: Radioresistance, which is a major cause of failure of radiotherapy (RT), is proposed as one of the intrinsic characteristics of cancer stem cells (CSCs) whose unique DNA damage response (DDR), efficient DNA repair and resistance to apoptosis are thought to confer the phenotype. We have isolated surviving CSCs by exposure to long-term fractionated radiation for 82 days from HepG2 and A172 cells (82FR-31NR cells). 82FR-31NR cells exhibited CSC properties, such as high expression of CSC marker CD133 and the ABC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 41 publications
6
55
0
Order By: Relevance
“…Cyclin D1 is also a key mediator that contributes to reduce cancer cell radiosensitivity via an established mechanism that facilitates G1-S cell cycle transition to improve cell self-renew and proliferation after irradiation (29)(30)(31). In the present study, cyclin D1 downregulation was observed in cells exposed to irradiation and cells transfected with miR-145 mimics was associated with considerable reduction of cell migration rate in wound healing assay.…”
supporting
confidence: 53%
“…Cyclin D1 is also a key mediator that contributes to reduce cancer cell radiosensitivity via an established mechanism that facilitates G1-S cell cycle transition to improve cell self-renew and proliferation after irradiation (29)(30)(31). In the present study, cyclin D1 downregulation was observed in cells exposed to irradiation and cells transfected with miR-145 mimics was associated with considerable reduction of cell migration rate in wound healing assay.…”
supporting
confidence: 53%
“…We previously reported that AKT regulated acquired radioresistance by tumor cells after long-term FR exposure [2] and the radioresistance of cancer stem cells [14]. Thus, the AKT pathway is a key to overcoming tumor radioresistance during RT.…”
Section: Discussionmentioning
confidence: 98%
“…Following radiation-induced damage of cells in tumors, many survival pathways are activated to protect cells from death. These pathways not only directly promote cell survival by increasing proliferation, invasion, and anti-apoptosis, but also contribute to improve the microenvironment, such as through angiogenesis [28][29][30][31]. Similarly, NPC can acquire resistance to radiation through antiapoptotic pathways by increasing DNA damage repair and through facilitating angiogenesis by enhancing ANG II.…”
Section: Discussionmentioning
confidence: 99%